ANALISIS ELEMEN BIAYA DALAM STRATEGI PENERAPAN HARGA PAKET WISATA EDUKASI TOPENG MALANGAN - Pribadi, Angelia; Nurim, Yavida; Harjanto, Nung (PPPM POLTESA, 2023)
Wayang topeng is one of the Indonesian arts inherited in Javanese society. This art is still a legacy of performing arts that is still being preserved in Malang, East Java. This art is known as the Malangan Mask. To continue to preserve the art of Malangan Mask, several artists established several dance studios located around Malang Regency. They also open tourism education for anyone interested in learning the art of Malangan Mask which has become the object of tourist visits. Based on observations by the Abdimas team to the Asmoro Bangun art padhepokan, this tour education is still difficult to determine the price of the right and affordable Malangan Mask Education tour package for tourists. So far, package pricing is only based on estimates, without formulating structured calculations. Furthermore, the method of implementing Abdimas is to conduct lectures on cost structure, as well as training and demonstration on setting the selling price of tour packages. The result of this Abdimas activity is the discovery of a solution for ticket pricing formulation through market research and identifying cost elements, calculating operational costs, and determining the amount of margin. Thus, this Abdimas activity succeeded in providing a strategy for calculating the selling price of the Malangan Mask Education Tour package.